2018
DOI: 10.7150/jca.28706
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases Pattern in Newly Diagnosed Metastatic Bladder Cancer: A Population-Based Study

Abstract: Purpose: Based on a large-population analysis, we aimed to estimate the incidence and survival of bone metastases (BM) in initial bladder cancer (BC) patients and to identify the risk and prognostic factors of BC patients with BM.Patients and methods: Using the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) database, bladder cancer patients diagnosed between 2010 and 2014 were retrieved. Multivariate logistic and Cox regression analyses were employed to identify risk factors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…A meta‐analysis carried out by Thompson et al 28 showed that poor differentiation was a risk factor for metastasis of cutaneous squamous cell carcinoma. Zhang et al 29 discovered that higher T stage, higher N stage, and poor tumor differentiation grade were positively related to bone metastases in initial bladder cancer. Similar conclusion was drawn in the study conducted by Moon 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis carried out by Thompson et al 28 showed that poor differentiation was a risk factor for metastasis of cutaneous squamous cell carcinoma. Zhang et al 29 discovered that higher T stage, higher N stage, and poor tumor differentiation grade were positively related to bone metastases in initial bladder cancer. Similar conclusion was drawn in the study conducted by Moon 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the risk factors was important for identifying patients at high risk for distant metastases [13,14] Results in our study revealed that patients with age younger than 67 years, male sex, T4 stage grade III, N1–3, histological subtype of EAC or others, and metastasis to liver, lung, and brain were more likely to have BM. These revealed risk factors can guide the identification of esophageal cancer patients with high risk of developing BM.…”
Section: Discussionmentioning
confidence: 99%
“…However, solid tumors can disrupt the delicate balance of bone physiology and result in an environment that promotes metastasis [24]. Recent studies reported the diverse homogeneous and heterogeneous associated factors in cancers correlated with bone metastasis [3,4,13,14]. Few studies have assessed the correlation between bone homeostasis and esophageal cancer, and further research is needed to identify the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We used the pathological grading standard according to the SEER database and previous studies. 15,16 The data for metastasis to distant lymph nodes, liver, lung, bone, and brain were identified at the time of diagnosis. The overall survival (OS) was considered as the endpoint.…”
Section: Study Variables and Endpointsmentioning
confidence: 99%